2005
DOI: 10.1590/s0100-879x2005000200011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of air pollution on pediatric respiratory emergency room visits and hospital admissions

Abstract: In order to assess the effect of air pollution on pediatric respiratory morbidity, we carried out a time series study using daily levels of PM 10 , SO 2 , NO 2 , ozone, and CO and daily numbers of pediatric respiratory emergency room visits and hospital admissions at the Children's Institute of the University of São Paulo Medical School, from August 1996 to August 1997. In this period there were 43,635 hospital emergency room visits, 4534 of which were due to lower respiratory tract disease. The total number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
0
18

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(89 citation statements)
references
References 35 publications
7
64
0
18
Order By: Relevance
“…Ninety articles (66%) deal with the adverse respiratory effects of air pollution of which 54 (60%) were selected 21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,…”
Section: Published Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ninety articles (66%) deal with the adverse respiratory effects of air pollution of which 54 (60%) were selected 21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,…”
Section: Published Articlesmentioning
confidence: 99%
“…Several time-series studies were conducted in metropolitan areas to investigate the health effects of air pollution 21,22,23,27,28,31,32,35,36,38,41,42,44,46,49,64,69,74 . Published in 2007, the first studies on the health effects of air pollution in biomass burning areas in the Brazilian Amazon were limited to descriptive studies and focused mainly on asthma 59,61,65,66,72 .…”
Section: (H)mentioning
confidence: 99%
“…Several authors have explored the deleterious effect of outdoor air pollution on pediatric respiratory morbidity [117,119,124] with decrease in lung function [106], with increased risk for asthma [111] and pneumonia in children [99,113] in urban areas like the cities of São Paulo [100,114,122,123], Rio de Janeiro [105], Curitiba [119] and Sobral [104]. Considering the lack of information on the air pollution effects on mortality in children's group, a study [121] showed the significant association between respiratory mortality in children and air pollution, in a city of SE Region.…”
Section: Regional -Regional Environmental Factorsmentioning
confidence: 99%
“…Copyright: © 2016 Chauhan et al Farhat et al (2005) [114] to assess the effect of air pollution on pediatric respiratory morbidity In the subtheme "exposure to chemical micropollutants", 15 articles (Tab. VI) were identified.…”
Section: A Study On Incidence Of Clinical Hypoxic Ischemic Encephalopmentioning
confidence: 99%
“…An association between daily ozone levels and respiratory symptoms has been reported (Romieu et al, 1996;Rabinovitch et al, 2004). Nevertheless, some authors have failed to note a significant relationship between ozone levels and morbidity (Atkinson et al, 1999;Farhat et al, 2005;Hinwood et al, 2006). Such differences are probably due to geographic reasons, although they may also be linked to the type of methodology employed.…”
Section: Introductionmentioning
confidence: 99%